Late Pleistocene Chronology of Sediments From the Yermak Plateau and Uncertainty in Dating Based on Geomagnetic Excursions. (10th July 2019) - Wiers, Steffen; Snowball, Ian; O'Regan, Matt; Almqvist, Bjarne
Abstract: The Yermak Plateau is one of several regions in the Arctic Ocean where paleomagnetism yields controversial results. Despite low sedimentation rates, late Pleistocene paleomagnetic excursions have been reconstructed from many cores in the region, but they are characterized by considerably longer durations when compared to established ones. Self‐reversal during maghemitization of (titano)magnetite has been proposed as one explanation. Rock magnetic, 14 C dating, sedimentological and stable isotope ( δ 18 O) methods were employed to three new sediment cores to put paleomagnetic results in the context of the regional stratigraphy and chronology. Coherence of lithological parameters and δ 18 O variations validated the ratio of anhysteretic remanent susceptibility to bulk magnetic susceptibility ( κ ARM / κ ) as a parameter for cross‐core correlation. As established by earlier studies, we use the link between glacial/interglacial cycles and κ ARM / κ to tune our records to a global δ 18 O stack, which provides age models that are independent of radicarbon ages and paleomagnetic data. Our results show that zones of negative magnetic inclination are asynchronous across the plateau. Alternating field demagnetization data revealed that negative inclinations are contained in a medium‐high‐coercivity (>25–35 mT) magnetic phase that may be the result of postdepositional alteration of (titano)magnetite. We note a positive relationship between water depth and excursion duration, which may be driven by changes in water mass circulation on glacial/interglacial timescales. Key Points: New paleomagnetic and rock magnetic data from the Yermak Plateau (Arctic Ocean) are presented We link variations in magnetic grain size to changes in global oxygen isotope stratigraphy to construct independent age models Based on our age model approach, reconstructed paleomagnetic excursions are asynchronous